The Shepherd of Hermas and the Pauline legacy - Soyars, Jonathan E. (Supplements to Novum Testamentum, 2019)
In The Shepherd of Hermas and the Pauline Legacy, Jonathan E. Soyars traces the influence of Pauline literary traditions upon one of the most widely attested and influential apocalyptic texts from early Christianity. Scholarship largely considers Hermas to have known very little about Pauline letters, but by looking beyond verbatim quotations Soyars discovers extensive evidence of his adoption, adaptation, and synthesis of identifiable Pauline material in the Visions, Mandates, and Similitudes sections. Hermas emerges as a Pauline interpreter who creatively engages topics and themes developed within and across the Pauline letters through time. These results reconnect the Shepherd with early Paulinism and extend reconstructions of the sphere of Pauline influence in the second century C.E.